2021
DOI: 10.3390/diagnostics11060942
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Three Slides Pap Test Compared to Punch Biopsy and Endocervical Curettage in Confirmed HSIL+ Diagnosis

Abstract: Objective: The aim of the study was to evaluate the accuracy of the diagnostic Pap test (DPT) on three slides and punch biopsy and endocervical curettage (PB/ECC) compared with the final biopsy material in the detection of high-grade squamous intraepithelial lesion (HSIL). Materials and methods: Patients treated with conization after previous DPT and PB/ECC were analyzed. The findings of the DPT and PB/ECC as well as of the endocervical brush cytology and ECC were compared with the final conus histology. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Maximiliano et al attempted to overcome the drawbacks associated with the sparseness of ECC tissue using cell concentration methods, which may be a suitable strategy for qualitative improvement of the sensitivity of ECC and its diagnostic value [ 27 ]. Furthermore, Rubesa-Mihaljevic et al found ECC sensitivity was higher for samples with abundant materials compared to samples with relatively few [ 28 ]. Uses of inexpensive and less painful sampling instruments to increase the rate of satisfactory specimen and reduce the reliance on senior physicians are additional ways of increasing patients’ compliance with procedures and improving lesion detection rates [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maximiliano et al attempted to overcome the drawbacks associated with the sparseness of ECC tissue using cell concentration methods, which may be a suitable strategy for qualitative improvement of the sensitivity of ECC and its diagnostic value [ 27 ]. Furthermore, Rubesa-Mihaljevic et al found ECC sensitivity was higher for samples with abundant materials compared to samples with relatively few [ 28 ]. Uses of inexpensive and less painful sampling instruments to increase the rate of satisfactory specimen and reduce the reliance on senior physicians are additional ways of increasing patients’ compliance with procedures and improving lesion detection rates [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one prospective study of 1,299 patients, there was a 72.4% diagnostic agreement between colposcopic targeted biopsy combined with ECC and specimens after cervical coning ( 10 ). In another study evaluating 150 patients with HSIL+ using the pathological results of postoperative conical specimens as the final criterion, colposcopic targeted biopsy combined with ECC had a 79% coincidence rate for a cervical HSIL+ diagnosis ( 11 ). In this current study, the diagnostic agreement rate of ECC combined with colposcopic targeted biopsy was higher than that of colposcopic targeted biopsy alone (72.43% vs. 67.54%).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, because of few inadequate samples in the 2 studies and because the rest of the included 5 studies excluded inadequate samples, this is not likely to be the reason for the diverging sensitivities of EB and ECC. In light of these findings, a recent study by Mihaljevic et al 31 has reported in a subanalysis that ECC samples with abundant material had higher sensitivity than those with scant material. We would have liked to have included this study, but some errors and inconsistencies were found in their 2Â2 tables, and the corresponding author did not reply to our e-mail.…”
Section: Systematic Reviewmentioning
confidence: 96%